Régulation et marchandisation de l’État par la fiscalité et la finance - Nicolas Pinsard (Revue de la Régulation)
This dissertation questions the process of formation and régulation – i.e., reproduction and modification – of the modern state through the taxation system and offices between the 12th and the 17th century in France. The analytical framework lies at the crossroad of Régulation Theory, market socio-economics, and economic and financial history. The method of this work is based on archival work and abduction. Offices are one of the main state organizations of that time and are also a royal delegation in essential state domains, including levying taxes. By analyzing the transformations of offices’ legal framework, the dissertation reveals that the regulation of state goes hand in hand with private appropriation and commodification of offices. The transformation of offices into patrimonial assets induces wealth accumulation for their owners and growth for royal revenues, during this period of transition between feudality and capitalism.